2006
DOI: 10.1124/jpet.106.110460
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction Improves Cardiovascular Risk Factors via Reduction of Mitochondrial Reactive Oxygen Species in Type II Diabetic Rats

Abstract: Uncoupling protein 2 (UCP2) is an important regulator of intracellular reactive oxygen species (ROS) production. We determined the effects of calorie restriction (CR) on the dynamic aspects of mitochondrial ROS production, UCP2, and the nitric oxide (NO)-cGMP pathway in the cardiovascular tissues of type II diabetic Otsuka Long-Evans Tokushima Fatty (OLETF) rats. Some rats were on restricted diets (30% reduction from free intake) from age 29 to 42 weeks. Blood glucose, hemoglobin A1c, plasma levels of free fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 35 publications
7
50
0
Order By: Relevance
“…14) However, mitochondrial reactive oxygen species (ROS) were reported to increase in the aortic and cardiac preparations from OLETF rats at 42 weeks of age. 29) Our study confirmed that inhibition of complex II by TTFA reduced superoxide production in the femoral artery of OLETF rats. We also found that GlycerAGEs increased superoxide production in the femoral artery from pravastatin-treated rats and this effect was inhibited by TTFA.…”
Section: )supporting
confidence: 77%
“…14) However, mitochondrial reactive oxygen species (ROS) were reported to increase in the aortic and cardiac preparations from OLETF rats at 42 weeks of age. 29) Our study confirmed that inhibition of complex II by TTFA reduced superoxide production in the femoral artery of OLETF rats. We also found that GlycerAGEs increased superoxide production in the femoral artery from pravastatin-treated rats and this effect was inhibited by TTFA.…”
Section: )supporting
confidence: 77%
“…Furthermore, CR attenuates the age-related impairment of the NO signaling system (Minamiyama et al 2007;Sharifi et al 2008;Yang et al 2004). However, it is unknown whether CR affects the H 2 S signaling system and whether CR specifically attenuates any affects of age on the H 2 S signaling system.…”
Section: Introductionmentioning
confidence: 99%
“…Caloric restriction is believed to reduce cardiovascular risk factors and slow down heart aging via reduction of mitochondrial reactive oxygen species in plasma and heart tissues (Minamiyama et al, 2007;Shinmura et al, 2011). On the other hand, several CR effects leading to alterations in gene expression and protein profile and deterioration of heart function have been reported (Katzeff et al, 1997;Sugizaki et al, 2009Sugizaki et al, , 2011Yamagishi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%